Ranking Factors for Supplier Selection with Application of the Ftopsis Method - Adis Puska; Sead Sadic; Admir I. Beganovic (Economic Review: Journal of Economics and Business, 2017)
The first step in starting each production is the choice of suppliers. The choice of suppliers is influenced by many factors that differ depending on whether it is the first relationship with suppliers or it is about establishing partnerships with suppliers. Factors influencing selection are different and depend on business cooperation with suppliers themselves. Unlike other works, this paper applies expert judgment in the rankings of supplier selection factors. Experts include those scientists who published scientific papers on this subject by the prestigious Elsevier publishing house. Experts were assigned a survey questionnaire containing 39 factors for supplier selection to which they gave their opinion on which of these factors is important for establishing new cooperation or establishing partnerships with suppliers. The answers received were processed and the factors were ranked using the fuzzy TOPSIS method. The results showed that various factors are used in this cooperation with suppliers.
Keywords: C50; L80; 330; Supplier selection; Expert opinion; Fuzzy TOPSIS